The reality of the electronic management at the University of Jeddah and its impact on organizational development - Almarzuqi, Maha Saleh; El Enein, Najwa Younes Abou (Journal of Economic, Administrative and Legal Sciences, 2019)
The objective of this study is to identify the reality of e- management at the University of Jeddah and its impact on organizational development through the study of three axes in organizational development: development of the organizational structure, human resources development and the employment of information technology in the university. The study was based on the analytical descriptive approach. A questionnaire was used on a random sample of male and female administrators at the University of Jeddah in the Kingdom of Saudi Arabia, where the number of those responding to the questionnaire was 60 individuals. The study found that individuals working at the University of Jeddah are aware of the advantages of electronic management and they are familiar with the university’s electronic applications such as e- mail and grading programs. There are also obstacles to the application of electronic management, including lack of human and technical capabilities necessary to implement electronic management. The study recommended the development of computerized administrative information systems to cover all administrative aspects, focusing on the development of electronic applications available and linking them to the workers in Jeddah University continuously, in line with the realization of the vision of the Kingdom 2030.